2018
DOI: 10.1016/j.psychres.2018.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Computational linguistic analysis applied to a semantic fluency task to measure derailment and tangentiality in schizophrenia

Abstract: Although rating scales to assess formal thought disorder exist, there are no objective, high-reliability instruments that can quantify and track it. This proof-of-concept study shows that CoVec, a new automated tool, is able to differentiate between controls and patients with schizophrenia with derailment and tangentiality. According to ratings from the derailment and tangentiality items of the Scale for the Assessment of Positive Symptoms, we divided the sample into three groups: controls, patients without fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
0
34
1
Order By: Relevance
“…This contrasts with our prediction based on findings of less coherent semantic VFT output in schizophrenia. 20 , 32 , 33 It may be important to test this hypothesis with longer periods of word generation, as differences in local cue salience may be subtle and difficult to detect within a 1-minute task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts with our prediction based on findings of less coherent semantic VFT output in schizophrenia. 20 , 32 , 33 It may be important to test this hypothesis with longer periods of word generation, as differences in local cue salience may be subtle and difficult to detect within a 1-minute task.…”
Section: Discussionmentioning
confidence: 99%
“…A common computational metric utilized in the present study is semantic coherence, defined as the average similarity between each word and all other words in a particular text or word list. Prior VFT research has reported decreased semantic coherence in individuals with schizophrenia compared to healthy individuals 20 and in patients with thought disorder symptoms compared to patients without these symptoms, 20 , 21 while accounting for the number of words produced. On the less clinically severe end of the psychotic spectrum, a VFT study found comparable levels of semantic coherence between individuals with and without schizotypal traits, 23 with fewer total responses among schizotypal individuals only under conditions with an affective load.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior research in linguistic analysis has identified significant differences at the word level in the use of certain word categories, as well as at the sentence level in terms of semantic density, coherence, and/or content, both in individuals at risk for developing psychotic disorders as well as those with established SSD and MD [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Language extracted from online search activity is distinct due to its short sentence structure and the unique nature of the online search platform.…”
Section: Plos Onementioning
confidence: 99%
“…Generally, open interviews were conducted in scenarios close to clinical settings, 45 while task-based assessment took place in artificial environments. 41 …”
Section: Resultsmentioning
confidence: 99%